Construção e aplicação de um sistema de liberação controlada/lenta baseada em bioconjugados de carbonato de cálcio e lectina de Dioclea violacea: efeito em células de câncer cervical - Osterne, Vinícius José da Silva (2020)
Lectins are proteins that bind specifically to carbohydrates and are able to form complexes with molecules containing saccharides without changing their structure. Because of the many biological activities displayed by these proteins, they have great applicability in biotechnology. Controlled/slow drug release technology is one of the most promising applications of nanotechnology for disease treatment and diagnosis because it overcomes several problems associated with the use of macromolecules such as proteins as drugs. In this context, the present investigation aimed to develop a system for the controlled release of Dioclea violacea lectin (DVL), a mannose/glucose-specific legume lectin with anticancer properties, by applying two different sizes of CaCO3 particles, a low-cost, broadly available and biocompatible compound. Results show that the systems are feasible and present desirable properties of adsorption and release. The application of the bioconjugates on HeLa cells indicates that the proposed system is effective as a cytotoxic agent against this cell type, even more than the free lectin. The present data demonstrate that the system has a potential application in cancer treatment and the methodology enables the use of other anticancer lectins/proteins.